Vesicouterine Fistula (Youssef Syndrome): Case Report and Literature Review - Machado Junior, Reynaldo Augusto; Machado Junior, Luís Carlos; Lourenço, Lúcio Lourenço e (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To describe a case of vesicouterine fistula and to review the literature related to this condition.Methods For the review, we accessed the MEDLINE, BIREME and LILACS databases; the references of the searched articles were also reviewed.Results A 38-year-old woman, in the 1st day after her 3rd cesarean, presented heavy hematuria, which was considered secondary to a difficult dissection of the bladder. A total of 6 months after delivery, she failed to resume her regular menstrual cycles and presented cyclic menouria and amenorrhea. At this time, she had two episodes of urethral obstruction by blood clots. She remained without a correct diagnosis until about two years postdelivery, when a vesicouterine fistula was confirmed through cystoscopy. A surgical correction through open abdominal route, coupled with hysterectomy, was performed. After the surgery, the symptoms disappeared. The review showed a tendency of change in the relative frequency of the different types of genitourinary fistulae. Vesicovaginal fistulae, usually caused by inadequate care during labor, are becoming less frequent than those secondary to medical procedures, such as vesicouterine fistulae. The most common cause of this latter kind of fistula is cesarean section, especially repeated cesarean sections. The diagnosis is confirmed through one or more imaging exams, or through cystoscopy. The most common treatment is surgical, and the routes are: open abdominal, laparoscopic, vaginal or robotic. There are some reports of success with the conservative treatment.Conclusion Vesicouterine fistulae are becoming more common because of the increase in the performance of cesarean sections, and the condition must be considered a possible complication thereof.
Keywords: cesarean section; repeat cesarean section; urinary incontinence; hematuria